Electrocatalytic nitrate and nitrous oxide reduction at interfaces between Pt-Pd nanoparticles and fluorine-doped tin oxide. (1st September 2022) - Sarker, Abinash Chandro; Kato, Masaru; Yagi, Ichizo
Highlights: Pt, Pd and PtPd nanoparticles are deposited on FTO by arc-plasma deposition. The PtPd/Sn interface has higher NO3 RR activity than the Pt/Sn or Pd/Sn interface. The PtPd/Sn interface also has higher N2 ORR activity. The PtPd/Sn interface shows no drastic contribution to NO2 RR and NORR. Abstract: We report the preparation of Pt and/or Pd nanoparticle-deposited fluorine-doped tin oxide (FTO) electrodes by an arc-plasma deposition (APD) technique and their electrocatalytic activity for nitrate (NO3 – ), nitrite (NO2 – ), nitric oxide (NO), and nitrous oxide (N2 O) reduction reactions in acidic media. Cyclic voltammetry of the electrodes revealed that the co-presence of Pt and Pd on FTO showed higher catalytic activity than Pt or Pd on FTO for the NO3 – reduction reaction, where the PtPd/Sn interface acts as the catalytic active site. The PtPd/Sn interface also showed higher catalytic activity for the N2 O reduction reaction to dinitrogen than the Pt/Sn or Pd/Sn interfaces, whereas it showed no drastic contribution to the electrocatalytic NO2 – and NO reduction reactions. Because the NO3 – and N2 O reduction reaction occur in the potential region of hydrogen adsorption on Pt and Pd electrodes, the PtPd/Sn interface could enhance NO3 – and N2 O adsorption and/or suppress the hydrogen adsorption. Our findings will be useful for the design of interfaces between noble metal mixture/alloy nanoparticles and Sn, leading to the practical application of denitrification to harmless dinitrogen. Graphical abstract: Image, graphical abstract